Women's Experience of the Transition from Technical Engineer to Manager and Leader - an Australian Study - Marinelli, Melissa (2010)
Linking into existing research in the areas of women in non-traditional work, management and leadership and engineering practice, this paper presents the initial stages of current research exploring the advancement of women engineers to managers and leaders in technical organisations. Using a qualitative methodology, informed by phenomenological and feminist perspectives, the research aims to provide an understanding of women engineers’ transition to manager and leader from the perspective of those that have lived it. This voice will broaden and enhance the existing view of management and leadership in engineering to guide policy and practice advancing women in the profession. This paper focuses on the motivation for the work and initial literature review, the development of the enquiry framework and research method, and ethical considerations for the project.